2016
DOI: 10.1103/physrevb.93.165422
|View full text |Cite
|
Sign up to set email alerts
|

Single-layerMoS2on Au(111): Band gap renormalization and substrate interaction

Abstract: The electronic structure of epitaxial single-layer MoS2 on Au(111) is investigated by angleresolved photoemission spectroscopy, scanning tunnelling spectroscopy, and first principles calculations. While the band dispersion of the supported single-layer is close to a free-standing layer in the vicinity of the valence band maximum atK and the calculated electronic band gap on Au (111) is similar to that calculated for the free-standing layer, significant modifications to the band structure are observed at other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
140
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(170 citation statements)
references
References 60 publications
(107 reference statements)
23
140
1
2
Order By: Relevance
“…Previous ARPES and density functional theory (DFT) calculation revealed that S 2p z orbitals of the lower S atoms in monolayer MoS 2 interact with d band of Au(111) surface, and strong overlap of S 2p z with Au sp band especially occurs when the lower S atoms is located on the on top position . The results mean that the S–Au interaction at the A site is significantly stronger than that at B and C sites.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous ARPES and density functional theory (DFT) calculation revealed that S 2p z orbitals of the lower S atoms in monolayer MoS 2 interact with d band of Au(111) surface, and strong overlap of S 2p z with Au sp band especially occurs when the lower S atoms is located on the on top position . The results mean that the S–Au interaction at the A site is significantly stronger than that at B and C sites.…”
Section: Resultsmentioning
confidence: 93%
“…STS measurements revealed that MoS 2 and MoSe 2 monolayers grown on monolayer graphene, bilayer graphene, or highly ordered pyrolytic graphite (HOPG) did not show any LDOS within the bandgap, and bandgap values of 2.15 eV or 2.40 eV (MoS 2 on HOPG), 2.2 eV (MoS 2 on monolayer graphene), and 2.18 eV (MoSe 2 on bilayer graphene) and 1.94 eV (MoSe 2 on HOPG) have been reported. Very recently, STS measurements also found that the bandgap values of MoS 2 /Au(111) become smaller than that of MoS 2 on graphene and are estimated to be 1.3 and 1.74 eV, respectively . DFT calculation also showed that the reduction of the bandgap values is attributed to be the strong interaction of lower S 2p z atoms with d band of Au surface, which causes a distortion of VBM of MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the states at theK point remain largely unperturbed. This can be explained by their inplane character [15] and the fact that theK point of MoS 2 lies in a projected bulk band gap of the Au substrate [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…By doing this, both the Au(111) and 2H-MoS 2 unit cell is matched with the ideal lattice constant of 1T'-MoS 2 monolayers. We should mention that this five-layer model has been adopted in previous works describing well some features observed in experiments [40,41].…”
Section: Theoretical Simulationsmentioning
confidence: 95%